DIGITAL PRODUCT PASSPORT AND BLOCKCHAIN: AN INTEGRATED APPROACH TO ENSURING PRODUCT TRACEABILITY - Avlokulova Sadokat Sobirjon kizi (Modern American Journals, 2025)
The growing demand for product transparency, sustainability, and circular economy practices has accelerated the development of Digital Product Passport (DPP) systems. This paper explores the integration of blockchain technology into DPP frameworks to enhance product traceability across the entire lifecycle — from raw material sourcing to end-of-life recycling. By leveraging blockchain's decentralized, immutable, and transparent nature, DPPs can ensure trustworthy data exchange among stakeholders while reducing the risk of fraud and data manipulation. The study analyzes the technical architecture, potential challenges, and real-world applications of blockchain-enabled DPPs, highlighting their role in promoting sustainable manufacturing, regulatory compliance, and consumer trust. Special attention is given to how this integrated approach can be adapted to emerging economies where digital infrastructure is evolving.
Keywords: Digital Product Passport (DPP), blockchain, Supply Chain Transparency, product traceability, circular economy, Smart Contracts, IoT, decentralization, sustainability